Efeito da fração proteolítica de Carica candamarsensis na cicatrização cutânea: avaliação pré-clínica fase I - Flavia Sampaio Latini Gomes (2009)
The purpose of this study was to evaluate the healing activity of the proteolyticfraction named P1G10 from Carica candamarcensis latex, when applied to skinburns previously induced in mice. The proposal also verified the safety andharmless effect of this fraction when applied to intact skin of healthy people,and the safety and healing rate of this fraction when applied to skin pressure orvenous ulcers of voluntary humans. Finally, the proposal aimed to develop asoftware to evaluate the digital images obtained from healing wounds treatedwith the active principle. Initially, the fraction was characterized for theconstancy of its proteolytic activity, and protein concentration. P1G10 fractionsused in these experiments was 8.39 ± 0.39 mg ml-1 and 13.5 ± 0.5 nM mg-1 min,respectively, thus assuring a constant protein content and proteolytic activityvalue for various experiments. The results of P1G10 on heat-induced, thirddegreeburn using the rodent model show that 0.1% P1G10 acceleratesepithelisation while the effect of 1% or 0.01% P1G10 is not significantly differentto 1% silver sulphadiazine, 2% papain or the hydrosoluble vehicle used ascontrol. In a double-blind randomized experiment comparing the healingresponse of 0.01%, 0.1% and the vehicle alone, we confirmed the enhancedhealing property of P1G10. Histological analysis of burn-tissue sectionsfollowing treatment with P1G10 support these observations. The clinical trialsin humans (phase 1) using double-blind protocols showed no visual evidence ofadverse skin effect at the site of application during one-month and no changesin blood (hemogram) and liver or kidney clinical parameters. The clinical trialsin humans (phase 2) using double-blind protocols showed no differencebetween the group treated with P1G10 and the control treated with 1.0% silversulfadiazine. The lack of significant healing effect by P1G10 is attributed to thesmall size of the sample (n =10). However a 60% decrease in perimeter size wasobserved in wounds treated with P1G10, while no effect was seen on woundstreated with silver sulfadiazine. The evaluation of the software aimed tocapture the images during wound healing demonstrated acceptable variationswhen repeated measurements were done by the same operator or when a singleimage was quantified by different operators. These results extend the healingproperties of these groups of enzymes to a different type of trauma (burns)while the results of clinical trials encourage future applications.